Study of differences between patients with schizophrenia and healthy people in semantic processing. Issue 5 (4th August 2021) - Ye, Huiling; Zhu, Xinyu; Wang, Kaifeng; Song, Lisheng; Yang, Xiaohu; Li, Fei; Fan, Qing
Abstract: Semantic processing is important in language comprehension and production, and context can facilitate understanding and accelerate processing speed by pre‐activating semantically related words. There are many studies suggesting that patients with schizophrenia have inferior language ability. This study was aimed to examine the differences between patients with schizophrenia and healthy people in semantic processing with Chinese classifier–noun pairs rating tasks. Participants were required to finish rating tasks to judge acceptability of classifier–noun pairs. Also, the Positive and Negative Syndrome Scale (PANSS) was conducted in the schizophrenia group. According to results of variance analysis, schizophrenic patients' accuracy of judgment on the acceptability of classifier–noun pairs differed from the control group ( F  = 4.13, p  < .05), and the contextual effect of classifier constraint could be observed in healthy people ( F (1, 31) = 5.38, p  < .05) but not in patients with schizophrenia ( F (1, 25) = 3.55, p  = .07), indicating that they failed to use the contextual information to facilitate language comprehension as healthy people. Stepwise linear regression analysis found that hostility, poor impulse control and suspiciousness/persecution and preoccupation in the PANSS may have contributed to the reduced sensitivity in the rating in patients ( t  = −2.38‐3.80, p  < .05).